Antiproliferative and apoptotic effects of pinocembrin in human prostate cancer cells - Chen, Zhenyu; Rasul, Azhar; Zhao, Chaoyue; Millimouno, Faya Martin; Tsuji, Ichiro; Yamamura, Takaki; Iqbal, Rehana; Malhi, Mahadev; Li, Xiaomeng; Li, Jiang (Bangladesh Journal of Pharmacology, 2013)
Pinocembrin, (5, 7-dihydroxyflavanone), has been shown to possess anticancer activity against various cancer cells. However, its effect against prostate cancer cells remained enigmatic. In this study, for the first time, we investigated whether pinocembrin could inhibit growth of human prostate cancer cells. MTT assay and flow cytometric analysis were performed to examine the effects of pinocembrin on cell proliferation, cell cycle, and apoptosis. The results revealed that pinocembrin attenuated the cell viability of both androgen-sensitive (LNCaP) as well as androgen-independent (PC3 and DU-145) prostate cancer cell lines, with different p53 status. Further characterization showed that pinocembrin markedly induced apoptosis of LNCaP cells and arrested cell cycle at S and G2/M phase and involved in the dissipation of mitochondrial membrane potential before culminating in apoptosis in pinocembrin-treated LNCaP cells. These in vitro results suggested that pinocembrin should be further examined for in vivo activity in human prostate cancer.